2016
DOI: 10.1007/s12325-016-0350-5
|View full text |Cite
|
Sign up to set email alerts
|

Substantial Effects of Luseogliflozin Revealed by Analyzing Responses to Postprandial Hyperglycemia: Post Hoc Subanalyses of a Randomized Controlled Study

Abstract: IntroductionIn our previous study investigating effects of luseogliflozin, a sodium–glucose cotransporter 2 inhibitor, on 24-h glycemic variability by continuous glucose monitoring (CGM), luseogliflozin elicited parallel downward shifts in fasting and postprandial glucose levels. However, further review of individual patients’ data revealed that postprandial hyperglycemia was not reduced in some patients, while preprandial glucose was ameliorated in most patients. Therefore, we divided patients into two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…However, the changes between time points can be approximated using the slope of a linear mixed-effects model. Linear mixed-effects methods are used to fit the model to repeated-measures data such as those of CGM [ 55 ], in which measurements are obtained repeatedly over time or under different conditions. The model comprises repeated effects, fixed or covariate effects, and random effects, and the interactions among combinations of these as predictor variables.…”
Section: Discussionmentioning
confidence: 99%
“…However, the changes between time points can be approximated using the slope of a linear mixed-effects model. Linear mixed-effects methods are used to fit the model to repeated-measures data such as those of CGM [ 55 ], in which measurements are obtained repeatedly over time or under different conditions. The model comprises repeated effects, fixed or covariate effects, and random effects, and the interactions among combinations of these as predictor variables.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, plasma insulin levels and the magnitude of insulin resistance were not described in that study. However, it has been shown that the use of the SGLT2i luseogliflozin reduced plasma insulin in type 2 diabetes (32). Given that the participants in the EMPA-REG OUTCOME trial had an average body mass index of 30.6 kg/m 2 at baseline and that the reduction in serum UA (observed as early as at 12 wk) was accompanied by a sharp decrease in hemoglobin A1C levels and in waist circumference (47), the hypouricemic effects of the SGLT2i may partly be attributable to reduced insulin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting GV has lond been recognized as most useful in treating T2DM patients in terms of both hyperglycemia management and risk reduction of vascular complications [41]. In this context, luseogliflozin has reportedly reduced glucose fluctuations in a randomized controlled trial in T2DM patients [42]. However, data are lacking with regard to other SGLT2i in that context.…”
Section: Glucose (Fasting and Postprandial)mentioning
confidence: 99%